ANALISIS PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN DI KOTA CIREBON - Feny Auliyah; Nur Rahman; Sarip Sarip; Althea Tahaanii Sutriana (Jurnal De Jure Muhammadiyah Cirebon, 2021)
This study aims to determine how the policy to prevent Covid-19 in the city of Cirebon, as well as to analyze how the policy is implemented in the community. This research is a type of normative legal research with an empirical approach, this study uses primary data as the main data, namely in the form of data taken directly from the field, through various observation processes. The results showed that the Covid-19 control policy in Cirebon was appropriate and referred to the policy issued by the West Java Regional Government, which was stated in Governor Regulation Number 60 of 2020 concerning the Application of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control Corona Virus Diseas 2019 is in the New Era Life Order, but at an empirical level, the level of community compliance in Cirebon City is still very minimal, especially for people living in areas far from the city center that have not fully enforced health protocols. So it is necessary that the Regional Government of Cirebon City can issue a policy as an alternative solution that can have an impact on the level of public compliance to continue to enforce health protocols in the new normal era. Keywords: Covid-19, New Era, Health Protocol.